THE EFFICACY OF HYALURONAN TREATMENT ON THE KNEE OSTEOARTHRITIS WITH EFFUSION: ONE YEAR PLACEBO CONTROLLED TRIAL - Melek Sezgin; Alev Çevikol Demirel; Özgür Ortancıl; Cevriye Karaca; Canan Çınar; Aytül Çakçı (Archives of Rheumatology, 2003)
The aim of the study was to investigate the efficacy of the intraarticular Hyaluronan (HA) treatment on the knee osteoarthritis (OA) with effusion. The study was one year duration, single blind, placebo controlled and randomized. Forty-one patients with primary knee OA were enrolled in the study. The patients were divided into two groups as drug and placebo groups. The patients in the drug group were administered intraarticular HA and the patients in the placebo group were administered intraarticular 0.9% NaCl, once a week, totally three times. Clinical efficacy was assessed by WOMAC pain, stiffness and physical function scores, 25 m walking time, knee flexion, effusion volume and measurement of knee circumference before the treatment, one week and one year after the treatment. While statistically significant decrease of the effusion was determined in the drug group (p=0.001), there was no difference in the placebo group (p=0.133) one week after the treatment. In the drug group in WOMAC stiffness score and measurement of knee circumference, statistically significant decrease were determined one year after treatment (p=0.001 and p=0.0001 respectively) but there was no difference in the placebo group (p=0.064 and p=0.349 respectively). In addition, 1 year after the treatment in the drug group in WOMAC physical function score, measurement of knee circumference and 25 m walking time, was found to be significantly better than placebo group except WOMAC pain score (p=0.317), and significant differences were found one year after the treatment (p<0.05). There was no any local or systemic reactions after the injections or in the follow-up period. Our study showed that HA treatment was superior to placebo in patients with knee OA with effusion, was safe and the efficacy lasted at least one year.